Finitude para pares de germes de aplicações Bi-K-bi-Lipschitz equivalentes - Sena Filho, Edvalter da Silva (2016)
In this paper, we analyze the behavior of equivalence classes provided by the relation Bi-K-bi-Lipschitz. We show that when we are working with germs pairs of polynomial applications (f; g) : (Rn; 0) ! (Rp Rq; 0), with degree of f1; :::; fp; g1; :::; gq less than or equal to k 2 N, we have only a fi nite number of equivalence classes. We will also show in this work that the sets of equivalence classes with respect to strongly bi-lipschitz relation is fi nite.